Implementasi Ketahanan Pangan Melalui Program Urban Farming di UMKM Emak Farm Hidroponik Sidoarjo - Andini Salsabilla; Rachmawati Novaria (Politeknik Kampar, 2023)
Food sustainability is one of the important issuees that has become a global challenge today. The Urban Farming program is one of the innovative solutionsts improve food sustainabilitiy, especially in urban enironments. Micro, Small, and Medium Enterprises (MSMEs) have an important role in improving food sustainability through urban farming. This study aims to assess the contribution of Urban Farming programs run by MSMes in improving food sustainability in urban environments. The rsearch methods used were qualitative and field survey. Data was obtained from MSMEs that have implemented the Urban Farming program. The results showed that the program can contribute to food sustainability. In addition, the program also has the potential to create jobs and increase MSME income. In a increasingly dense urban context, the Urban Farming program can be a sustainable solution to address food security challengs